Pengaruh Substitusi Tepung Jagung (Zea mays L.) Pada Tepung Terigu Terhadap Karakteristik Biskuit MP-ASI Daun Katuk (Sauropus androgynus L.) - Aulia Hafsah, Riska Fauziah (Jurnal Dimamu, 2025)
Complementary foods for breast milk (MP-ASI) are complementary foods for breast milk that are made to help meet the nutritional needs of babies. The aim of this research is to obtain the right substitute for corn flour to obtain water content, carbohydrate content, phosphorus and organoleptic content. This study used a Randomized Block Design (RBD) consisting of 6 treatments and 4 replication. The research data is collected, then processed using analysis of variance (ANOVA). If there are significant differences, then followed by Duncan’s multiple range test. The results of the research showed that the best substitution treatment or corn flour for wheat flour on the characteristics of katuk leaf MP-ASI biscuits was found in treatment C (30:70) with a water content of 4,77%, carbohydrate content of 21,37%, phosphorus of 111mg/30g, a dissolving time of 42,46 second, and a preference level value for taste, aroma, color, and texture respectively were 3,62 (neutral to like, 3,69(neutral to like), 3,89 (neutral to like), 3,67 (neutral to like). This determination is based on the resultof the bayes test.